Analisis Strategi Pengembangan Usaha dan Pemasaran Produk Pada Usaha Narasa Potato - Lusi Ketrin Memah; Suryadi Samudra; Harnida Wahyuni Adda (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The food and beverage business in Indonesia is a business that continues to grow. Seeing the increasing number of restaurants, cafes and other culinary attractions, this indicates that the food and beverage business is always eyed by all parties. The goal of Narasa Potato product development is to maximize product sales achievement and also to increase customer satisfaction with Narasa Potato products. At present there are also many businesses that have recently opened and then closed because they have not thought about the existing market competition. This study aims to analyze the business development strategy and product marketing at the "Narasa Potato" business. The research method used is qualitative with data processing and analysis consisting of primary data analysis in the form of interview data and secondary data in the form of information about Narasa Potato products. attract and target the market by continuing to market products through today’s modern technology network so that Narasa Potato products are increasingly known and remain viable in the current era of market competition by implementing better business development and product marketing.